- MODEL MIKRO-DIFERENSIASI KURIKULUM BERBASIS PROFIL KEBUTUHAN PESERTA DIDIK DENGAN HAMBATAN INTELEKTUAL DI SEKOLAH DASAR INKLUSIF: - - Dyah Tri Untari; Mona Monica Diky Saputri; Choiriyah Widyasari (JPI (Jurnal Pendidikan Inklusi), 2026)
This study aims to formulate an initial curriculum micro-differentiation model based on learner need profiles for students with intellectual disabilities in an inclusive elementary school. The research was conducted at SDN 03 Girimulyo, Karanganyar, Central Java, using a descriptive qualitative approach with a case-study design. Data were collected through classroom observation, semi-structured interviews with teachers and school personnel, and document review. The data were analyzed through reflective needs analysis involving data reduction, categorization, interpretation, cross-source verification, and model formulation. The findings show that the school has provided inclusive access and direct classroom support, such as repeating instructions, reducing assignment volume, providing concrete examples, and giving individual assistance. However, these supports have not been organized into a written and sustainable system for mapping needs, setting essential learning targets, modifying content, adapting learning processes, varying learning products, and monitoring progress. The proposed model consists of six interrelated components: initial mapping, essential target setting, content modification, process adaptation, product variation, and progress monitoring. Theoretically, this model does not replace differentiated instruction theory; rather, it strengthens it by offering a micro-level operational framework that is more feasible for inclusive elementary classrooms with limited resources. Practically, the model helps teachers move from spontaneous assistance toward documented, realistic, and continuous inclusive services. Keywords: curriculum differentiation, inclusive education, intellectual disability, learner profile, elementary school